RELATIONSHIP BETWEEN SELF-MANAGEMENT AND QUALITY OF LIFE OF HYPERTENSION PATIENTS AT SLEMPIT KEDAMEAN COMMUNITY HEALTH CENTER - Dwi Ismawati; Diah Jerita Eka Sari; Diah Fauzia Zuhroh; Ervi Suminar (OJS Universitas Muhammadiyah Gresik, 2025)
Hypertension is often called the silent killer because many hypertension sufferers do not understand the signs and symptoms of hypertension before being examined. So Self-Management is one way to minimize complications that can disrupt a person's quality of life. Intervention in handling hypertension independently is very necessary to minimize the cost of patient treatment, there are several efforts to carry out Self-Management interventions independently. Such as changing and maintaining a healthier lifestyle, stopping smoking and alcohol consumption habits, doing a healthy diet, filling free time with exercise.